A comparison of open access in Exercise Science Journals: 2010 to 2012 - Rattray, B.; Cooke, J.; Bail, K.; Ranse, J. (The Open Sports Sciences Journal, 2013)
The aim of this study was to complete an audit on the number of open access journals within the discipline of Exercise Science. Publishing in open access journals results in wide dissemination of material in a very short period of time compared with the more traditional way of publishing in a subscription journal. The 2010 ERA journal list, category Human Movement and Sport Science, was initially utilised and then compared with the openness of the same journals in 2012.